Pengenalan Komputer - Prilly Ratag; Revalina N. Weku; Keysyah Lintang; Naysilla Suleman; Intan Sarayar; Regina Pinangkaan; Novita Sumondakh (STIKES Columbia Asia Medan, 2024)
This paper provides an introduction to computers, explaining their essential components, types, and functions. The study explores how computers have become an indispensable tool in daily life, from personal tasks to complex industrial processes. Emphasis is placed on understanding the basic hardware and software components, and the different types of computers available in the market today. The paper also highlights the importance of computer literacy in the modern era.